DEFINING AND MODELING RISKS IN SERVICE SUPPLY CHAINS - SerdarAsan, Seyda; Karadayı-Usta, Saliha (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Risk management in supply chains is of growing importance and has been studied extensively in manufacturing supply chains. However, risk in service supply chains (SSCs) is largely neglected. Since SSCs are not immune to disruptions, there is a need to study and understand supply chain risks from a service perspective. This paper sets out to identify, define and examine risks in SSCs. Using a systematic literature review, the paper explicitly defines seven risk types associated with SSCs: financial, relationship, demand, operational, service delivery, Information technology (IT), and external risks. To gain a deeper understanding of these risks and their consequences, a structural model of the relationships among them was developed using ISM and MICMAC. This study helps us to identify and understand all the risks that need to be assessed in SSCs, which in turn would lead to enhanced risk management and business sustainability.